(3x − 5) − (4x + 6)
Pretend that there is a 1 in front of the first bracket.
Pretend that there is a -1 in front of the second bracket.
Multiply the first bracket by 1
(1)(3x)=3x, (1)(-5)=-5
Multiply the second bracket by -1
(-1)(4)=-4, (-1)(6)=-6
3x-5-4x-6
3x-4x-5-6 ( combine like terms)
-x-11
Answer: -x-11 or -11-x
Answer:
the 3rd A
Step-by-step explanation:
ABACB = 5 altogether
ABACB ABA = 8
The length of the KN is 4.4
Step-by-step explanation:
We know from Pythagoras theorem
In a right angle ΔLMN
Base² + perpendicular² = hypotenuse
²
From the properties of triangle we also know that altitudes are ⊥ on the sides they fall.
Hence ∠LKM = ∠NKM = 90
°
Given values-
LM=12
LK=10
Let KN be “s”
⇒LN= LK + KN
⇒LN= 10+x eq 1
Coming to the Δ LKM
⇒LK²+MK²= LM²
⇒MK²= 12²-10²
⇒MK²= 44 eq 2
Now in Δ MKN
⇒MK²+ KN²= MN²
⇒44+s²= MN² eq 3
In Δ LMN
⇒LM²+MN²= LN²
Using the values of MN² and LN² from the previous equations
⇒12² + 44+s²= (10+s)
²
⇒144+44+s²= 100+s²+20s
⇒188+s²= 100+s²+20s cancelling the common term “s²”
⇒20s= 188-100
∴ s= 4.4
Hence the value of KN is 4.4
Answer:
36
Step-by-step explanation:
Divide the carton weight by the weight of 1 jar
27 ÷
= 27 ×
=
=
= 36
There are 36 jars in a carton